The Effect of Implementing the Talking Stick Method on Mastering Ilm al-Sarf in the First Grade at Wali Songo Islamic Institute - Nurul Azizah; Muhammad Sayifullah; Dian Risky Amalia (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2026)
This study was conducted in response to the low level of understading of ilm al-sarf among fisrt-level studens in Islmaic Boarding School environments. The aim of this research is to determine the effect of using the